MAKKIYYAH DAN MADANIYYAH PADA HADIS Upaya Menemukan Konsep Makki - Novriadi, Reno; Abror, Indal (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
The theory of Makkiyyah and Madaniyyah, which is formed as the implication of the historical background of the Qur’an, which went through phases of Mecca and Medina, is primarily known in the Qur’anic studies. Given that the hadith is also a primary source of Islam after the Qur'an, and is also framed in the same history as the Qur’an, this paper attempts to develop a theory of Makkiyyah and Madaniyyah in hadith. It argues that such theory in the Qur'an can be adopted into the study of hadith.